Engineering of Landau-Zener tunneling - Tayebirad, Ghazal; Mannella, R.; Wimberger, Sandro (Applied physics. B, Lasers and optics, 2011)
Several ways are discussed to control the Landau-Zener tunneling in the Wannier-Stark system. We focus on a realization of this system with interacting and noninteracting ultracold bosons. The tunneling from the ground band to the continuum is shown to depend crucially on the initial condition and system parameters and, more interestingly, on added time-dependent disorder—noise—on the lattice beams.
Gesehen am 30.06.2020